Transitions : The Development of Children of Immigrants - Marks, Amy Kerivan; Abo-Zena, Mona M.; Suárez-Orozco, Carola, 1957- (Book collections on Project MUSE., 2015)
Winner Best Edited Book Award presented by the Society for Research on AdolescenceImmigration to the United States has reached historic numbers-- 25 percent of children under the age of 18 have an immigrant parent, and this number is projected to grow to one in three by 2050. These children have become a significant part of our national tapestry, and how they fare is deeply intertwined with the future of our nation. Immigrant children and the children of immigrants face unique developmental challenges. Navigating two distinct cultures at once, immigrant-origin children have no expert guides to lead them through the process. Instead, they find themselves acting as guides for their parents.How are immigrant children like all other children, and how are they unique? What challenges as well as what opportunities do their circumstances present for their development? What characteristics are they likely to share because they have immigrant parents, and what characteristics are unique to specific groups of origin? How are children of first-generation immigrants different from those of second-generation immigrants? Transitions offers comprehensive coverage of the field's best scholarship on the development of immigrant children, providing an overview of what the field needs to know--or at least systematically begin to ask--about the immigrant child and adolescent from a developmental perspective.This book takes an interdisciplinary perspective to consider how personal, social, and structural factors interact to determine a variety of trajectories of development. The editors have curated contributions from experts across a carefully selected variety of topics covering ecologies, processes, and outcomes of development pertinent to immigrant origin children.